Impact of Reinforcement Corrosion on Progressive Collapse Behavior of Multi-Story RC Frames - Luchuan Ding; Xiaodi Dai; Yiping Gan; Yihua Zeng (Buildings, 2025)
The progressive collapse performance of reinforced concrete (RC) building structures has been extensively investigated using the alternate load path method. However, most studies have focused on newly designed structures, with limited attention given to existing buildings. Since progressive collapse can occur at any point during a structure’s service life and at various locations within the structural system, this study examines the progressive collapse behavior of deteriorated RC frames subjected to simulated reinforcement corrosion. This paper presents an investigation into the system-level progressive collapse responses of deteriorated RC frames, which extends the current state of the art in this field. The influence of different material deteriorations, different corrosion locations, different column removal scenarios, and dynamic effects on structural response is explored. According to the results obtained in this research, a significant reduction in progressive collapse resistance can be resulted in with increasing corrosion levels. Notably, only reinforcement corrosion in the beams located directly above the removed column (i.e., within the directly affected part) for the investigated RC frame had a substantial impact on structural performance. In contrast, corrosion in other regions and concrete deterioration exhibited minimal influence in this work. An increased number of corroded floors further reduced collapse resistance. Dynamic progressive collapse resistance was found to be considerably lower than its static counterpart and decreased at a slightly faster rate as corrosion progressed. Additionally, the energy-based method was shown to provide a reasonable approximation of the maximum dynamic responses at different corrosion levels, offering a computationally efficient alternative to full dynamic analysis.